CAPACITY OF DEVICES OF BITWISE ADDITION IN AM-CALCULATION SYSTEMS - Azarov, Oleksiy; Cherniak, Oleksandr (Scientific Works of Vinnytsia National Technical University, 2015)
This paper considers the class of calculation systems with additive and multiplicative correlations between the digit weights. There had been described the bitwise addition in such systems of calculation and the boundaries, within which the capacity of bitwise summators are, had been determined.